2019
DOI: 10.1002/cti2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactive antibody‐dependent cellular cytotoxicity antibodies are increased by recent infection in a household study of influenza transmission

Abstract: Objectives Influenza causes a spectrum of disease from asymptomatic infection to fatal outcome, and pre‐existing immunity can alter susceptibility and disease severity. In a household transmission study, we recruited outpatients with confirmed influenza virus infection and prospectively identified secondary infections in their household contacts, therefore identifying infection cases with baseline samples for determining immune‐mediated protection from influenza infection. Methods We examined baseline broadly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…1D ). To further assess ADCC responses at baseline before infection, we used pre H1N1 infection samples (Positive) from a household study and compared responses to household members who did not become infected (Negative) [ 3 ]. We did not find a difference in the profile of H1-HA targeted peptides between uninfected (Negative) and H1N1 infected (Positive) household contacts at baseline to account for acquisition of infection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1D ). To further assess ADCC responses at baseline before infection, we used pre H1N1 infection samples (Positive) from a household study and compared responses to household members who did not become infected (Negative) [ 3 ]. We did not find a difference in the profile of H1-HA targeted peptides between uninfected (Negative) and H1N1 infected (Positive) household contacts at baseline to account for acquisition of infection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vaccination of mice with ADCC activating peptides provided moderate protection, in terms of survival, viral loads and lung inflammation from homologous influenza virus challenge. Whilst peptide vaccination did not achieve the level of protection afforded by full H1-HA protein vaccination, it did demonstrate the protective potential of ADCC responses which has also been evident in human studies [ 1 , 3 ]. A limitation of our study is the reductionist approach of using linear peptides to identify antibody epitopes, as conformational epitopes may also play a role in influenza-ADCC responses.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 51 Regarding the latter, a recent longitudinal study showed that increased levels of antibodies capable of facilitating ADCC decreases susceptibility to influenza infection. 52 There is optimism that the same might hold true during infection with SARS-CoV-2 53 . Moreover, Bongen et al.…”
Section: Human Respiratory Virusesmentioning
confidence: 99%